Stimulating critical thinking through mathematics word problems (2011)
Mathematics is one of the most important subjects taught in all schools, it has a universal language that requires reading comprehension skills to be able to solve word problems. This action research reveals the use of critical thinking strategies with second grade students attending academic learning support, in a well recognize IB bilingual school in Bogotá. The purpose of this research is to support students attending mathematics learning to develop mathematics thinking skill through the comprehension of word problems in a second language that is English. With the implementation of thinking strategies such as to reading the problems and look for meaningful information, underlining key words and by visualizing the problem, students stimulate their learning process and become critical thinkers in the comprehension of mathematics word problems. These strategies tended to increased students confidence in solving word problems and become more competent mathematicians.(ABSTRACT FROM AUTHOR)